â€œLaper Kuprerâ€ dalam Pembelajaran Pendidikan Agama Islam Kompetensi Alquran - Futihatun Futihatun (Balai Diklat Keagamaan Semarang, 2023)
This research is descriptive qualitative research, with the aim of understanding the process of teaching and learning activities in Al-Quran competencies in Islamic Religious and Character Education, as well as efforts to activate students by learning using teaching aids, in the form of posters. This research uses observational research, focus groups, and document analysis. Learning uses teaching aids. The material contained in the teaching aids is discussed through group discussions and presented using gadget technology to record and share the recordings on familiar social media, known to students. This learning is termed